(untitled) (LINGUISTIK TERAPAN, 2021)
ABSTRACT The objective of this research is to explain wheter are students™ writing achievement taught by using collaborative writing technique is higher than that taught by using brainstorming writing technique. Because students more than active to make writing cooperatively. While the brainstorming writing technique ordered the students to make writing individually. The research design was experimental with research by using factorial design 2 x 2. There were 34 students from 2020/2021 academic year of Madrasah Aliyah Swasta Awashliyah 30 Binjai as the sample of this research.the students were divided into two groups. The first group was treated by using collaborative writing technique and the second group was treated by using brainstoring writing technique in writing achievement. The data were analyzed by applying ANNOVA. The result of the research that student™s writing achievement high curiosity with the mean score 83.35 higher than those with low curiosity eith the mean score is 82,29 and the Fobserved = 65.680 > Ftable 0.002. It means that students with high curiosity affect students writing achievement higher than students with low curiosity. Keywords: Writing TeachingTechniques, Students™ Curiosity, Writing Achievement